1992
DOI: 10.3354/meps082065
|View full text |Cite
|
Sign up to set email alerts
|

NH4+ regeneration and grazing: interdependent processes n size-fractionated 15NH4+ experiments

Abstract: We measured size-dependent NH,' regeneration by 15N isotope dilution on a seasonal basis in the plume of the Chesapeake Bay estuary (USA) using several different approaches. In our short-term (1 h) size-fractionation experiments, the mean rate of NH,' regeneration by total or by c 202 pm plankton increased from winter to summer a s a linear function of temperature. On the other hand, the mean NH,' regeneration rate by c 10 pm plankton was lowest in February, increased nearly 10-fold from February to April, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…We infer from these results and simple measurements of community structure on the basis of size fractionation that the size and species composition of the community are important variables in determining the rate of DON release. Because of the lack of complete correlation between trophic structure and organism size (Glibert et al 1992), it is not possible to interpret these results completely on the basis of the chl a and PN information collected with these experiments. In order to test some of the hypotheses described above as explanations for the observed patterns of PN and DON production, and of the effect of different size fractions in increasing or decreasing rates, it may be necessary to focus more specifically on the actual species composition of the community.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We infer from these results and simple measurements of community structure on the basis of size fractionation that the size and species composition of the community are important variables in determining the rate of DON release. Because of the lack of complete correlation between trophic structure and organism size (Glibert et al 1992), it is not possible to interpret these results completely on the basis of the chl a and PN information collected with these experiments. In order to test some of the hypotheses described above as explanations for the observed patterns of PN and DON production, and of the effect of different size fractions in increasing or decreasing rates, it may be necessary to focus more specifically on the actual species composition of the community.…”
Section: Discussionmentioning
confidence: 86%
“…These correlations are compelling evidence that DON release results from trophic dynamic interactions such as grazing and excretion, rather than from an experimental artifact. Glibert et al (1992) used size fractionation experiments to investigate the dependence of NH 4 + regeneration on grazing. They reported that NH 4 + regeneration rates in small fractions sometimes greatly exceeded the rates when the larger fraction, presumably containing the grazers, was present.…”
Section: Implication Of Grazing In Nitrogenous Nutrient Regenerationmentioning
confidence: 99%
“…Generally, microzooplankton are responsible for the bulk of NH,+ regenerated in a range of systems, including summer in Chesapeake Bay (e.g. Harrison 1978, Glibert et al 1992. However, the low C:N ratio of released DON we measured suggests that this material would be a substrate that would promote bacterial regeneration of NH4+ (Goldman et al 1987, Jargensen et al 1993.…”
Section: Experimental Considerations and Assumptionsmentioning
confidence: 83%
“…By 30 h, however, the ratios of DON release to NH,+ uptake had increased to 0.31 and 0.53 in the <202 pm and 1.2 pm plankton respectively. Rates of NH,+ regeneration have been shown to be higher in size-fractionated plankton samples, compared to whole plankton assemblages; the extent of this effect is in part a function of the density of the largest grazers (Glibert et al 1992).…”
Section: Time Of Daymentioning
confidence: 99%